Gastric adenocarcinoma: the role of Helicobacter pylori in pathogenesis and prevention efforts. Issue 1090 (24th May 2016) - Laird-Fick, Heather S; Saini, Shivani; Hillard, James Randolph
Abstract: Gastric cancer is the third most common cause of cancer deaths in the world, prompting high-risk countries like South Korea and Japan to establish nationwide screening programmes. Helicobacter pylori is linked to the majority of gastric adenocarcinoma cases and to the vast majority of non-cardia gastric adenocarcinomas. Several studies have demonstrated the effectiveness of 'test-and-treat' programmes for H. pylori infection to prevent gastric cancer in high-risk populations. While this strategy has gained momentum, providers in low-risk developed countries may be unaware of the risk individual patients face, particularly those who have emigrated from high-risk regions and members of economically disadvantaged minority groups. Rapidly evolving science in recent years has made it difficult for clinicians to keep up with the current best practices. This article reviews the epidemiology of H. pylori and gastric cancer, screening and diagnostic tests and the current treatment regimens for clinicians.